Hubungan Durasi Kerja dan Postur Tubuh dengan Keluhan Low Back Pain (Lbp) Penjahit di Nagari Simpang Kapuak Kabupaten Lima Puluh Kota - Burhan Muslim; Shalsa Devira; Basuki Ario Seno; Darwel Darwel; Erdinur Erdinur (Jurnal Sehat Mandiri, 2021)
Low Back Pain (LBP) is pain in the waist or lower spine that can be felt up to the buttocks and thighs. Many workers experience illness. Results The study was conducted on 9,482 workers in 12 regencies and cities in Indonesia, the disease experienced by workers was Musculoskeletal Disorder as much as 16% including Low Back Pain. This study aims to determine the relationship between work duration and work posture with complaints of Low Back Pain at Nagari Simpang Kapuak tailors, Lima Puluh Kota Regency. This research is quantitative with a cross sectional approach. Collecting data through a census of 43 tailors with interviews and questionnaires. Data analysis with univariate, bivariate and Chi-Square statistical test. The results of the study found that 58.1% of tailors experienced severe complaints of low back pain. 72.1% are classified as risky age, 74.1% are female, 58.1% have a BMI at risk, 67.4% work with risky work duration, 69.8% work with risky work postures. There is a relationship between age (p = 0.017), BMI (p = 0.013), work duration (p = 0.002), and body posture (p = 0.006) with complaints of Low Back Pain. To reduce the risk of Low Back Pain, tailors should relax and rest by stretching muscles, exercising based on the age of the worker, consuming foods that contain calcium, working with a balanced working time and doing an ergonomic work system.